2022
DOI: 10.9734/ejmp/2022/v33i330453
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Composite Mixture of Senna siamea Leaves and Tamarind Pulp Extracts on Multidrug Resistant Salmonella typhi

Abstract: Background: For many years, antimicrobial chemotherapeutic approach have been challenged by drugs resistant bacteria such as Salmonella associated with gastrointestinal infections. To overcome these effects, several attempts by herbalists and traditional healers were in progress, using some plants parts to treat Typhoid fever in Nigeria. Aim: The aim of this work was to determine the antibacterial activity of Senna siamea leaves and Tamarindus indica fruit pulp against multidrug resistant Salmonella typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Drug resistance is highly linked to virulence of microorganisms. Some variants of Salmonella have developed Multi-Drug Resistance and virulence genes as an integral part of the genetic material of the organism, and are therefore likely to retain their drug-resistant and virulent genes even when antimicrobial drugs are no longer used [30]. ).…”
Section: Resultsmentioning
confidence: 99%
“…Drug resistance is highly linked to virulence of microorganisms. Some variants of Salmonella have developed Multi-Drug Resistance and virulence genes as an integral part of the genetic material of the organism, and are therefore likely to retain their drug-resistant and virulent genes even when antimicrobial drugs are no longer used [30]. ).…”
Section: Resultsmentioning
confidence: 99%
“…The leaf extracts were found to contain saponins, tannins, glycoside, steroids, quinones, flavonoids, terpenoids, and alkaloids (Table 2). [25] reported the phytochemical analysis of Lawsonia inermis which showed the presence of quinones, saponins, tannins, flavonoids, terpenoids, glycosides and, alkaloids which all have good sources of antimicrobial and antioxidant activity [26,27,19]. It was observed that all the extracts showed prominent antibacterial activity.…”
Section: Phytochemical Screening Of the Plant Leaf Extractsmentioning
confidence: 99%